Обнаружение бычка-каспиосомы — Caspiosoma caspium (Кеsslег) в Днестровском лимане - Страутман, И.Ф.; Пинчук, В.И. (Вестник зоологии, 1972)
Caspiosoma caspium (К e s s l e r, 1877), which was not known from the basin of the Black sea westward of the Berezanian estuary, was found in the Dniester estuary. 11 specimen of this species including well preserved ones, were found when analysing the nutrition of big gobies Neogobius syrman (N o r d m.), N. kessleri G u n t r and Mesogobius gymnotrachelus (К e s s l.).